(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
According to available data (statistical data, data from investigations, professional and scientific papers) property crime represents about two thirds of total crime in the Republic of Croatia. Proof of committing is very often based on personal sources of evidence and a significant number of criminal charges filed by the police with these criminal offenses are submitted to the State Attorney’s Office. This article presents the state of affairs and trends of property crime, the way of proof, and analyzes the police’s success in detecting and proving serious offenses (Article 229. of the Criminal Code). The work is based on the collected data from the police records of Aggravated Larceny crimes, with special emphasis on the suspect’s interrogation based on Article 208a of the Criminal Procedure Act and the significance of the evidence thus obtained for proving the perpetration of the criminal offense. The research was conducted with the aim of determining the effects of the recently transposed Directive 2013/48/EU of the European Parliament and of the Council of 22 October 2013 on the right of access to a lawyer in criminal proceedings and in European arrest warrant proceedings, and on the right to have a third party informed upon deprivation of liberty and to communicate with third persons and with consular authorities while deprived of liberty (OJ L 294) into the criminal justice system of the Republic of Croatia.